Standardized home blood pressure monitoring: Rationale behind the 722 protocol - Lin, Hung Ju; Pan, Heng Yu; Chen, Chen Huan; Cheng, Hao Min; Chia, Yook Chin *; Sogunuru, Guru Prasad; Tay, Jam Chin; Turana, Yuda; Verma, Narsingh; Kario, Kazuomi; Wang, Tzung-Dau (Wiley, 2022)
Home blood pressure (HBP) has been recognized as a prognostic predictor for cardiovascular events, and integrated into the diagnosis and management of hypertension. With increasing accessibility of oscillometric blood pressure devices, HBP monitoring is easy to perform, more likely to obtain reliable estimation of blood pressures, and feasible to document long-term blood pressure variations, compared to office and ambulatory blood pressures. To obtain reliable HBP estimates, a standardized HBP monitoring protocol is essential. A consensus regarding the optimal duration and frequency of HBP monitoring is yet to be established. Based on the current evidence, the "722" protocol, which stands for two measurements on one occasion, two occasions a day (morning and evening), and over a consecutive of 7 days, is most commonly used in clinical studies and recommended in relevant guidelines and consensus documents. HBP monitoring based on the "722" protocol fulfills the minimal requirement of blood pressure measurements to achieve agreement of blood pressure classifications defined by office blood pressures and to predict cardiovascular risks. In the Taiwan HBP consensus, the frequency of repeating the "722" protocol of HBP monitoring according to different scenarios of hypertension management, from every 2 weeks to 3 months, is recommended. It is reasonable to conclude that the "722" protocol for HBP monitoring is clinically justified and can serve as a basis for standardized HBP monitoring.